Answer:
-3 = x
Step-by-step explanation:
0 = -x3-9
9=-x3
3=-x
-3=x
Hi there!
The whole race would've been 8 hours long.
Could you Brainliest me please?
The correct answer will be 5z^3
Answer:
a(6) = 37.97
Step-by-step explanation:
If the first term a(1) is 5 and the common ratio r is 3/2, then the general formula for this geometric sequence is
a(n) = 5*r^(n - 1).
Thus, the 6th term is a(6) = 5*(3/2)^(6 - 1), or a(6) = 5(3/2)^5 = 37.97
Answer:
C. y = x^2 -10x +26
Step-by-step explanation:
The translated function is ...
g(x) = f(x - right) + up
g(x) = f(x -5) +1
g(x) = (x -5)^2 +1
g(x) = x^2 -10x +26
In "y =" form, this is ...
y = x^2 -10x +26 . . . . matches choice C